Thermal, mechanical, and rheological properties of biodegradable polybutylene succinate/carbon nanotubes nanocomposites - Ali, Fathilah; Mohan, Raja (Wiley InterScience, 2010)

(untitled)
Biodegradable poly(butylene succinate)/carbon nanotubes nanocomposites were prepared by melt mixing process and the influence of carbon nanotubes on the properties of the nanocomposites was investigated. Differential scanning calorimetry showed that crystallization temperature (Tc) increase with increasing carbon nanotube content. Improvement of tensile modulus was observed by the addition of carbon nanotubes compared to pure poly(butylene succinate). Electrical conductivity showed that conductivity of polybutylene succinate/carbon nanotube composites increased with addition of carbon nanotube content. The storage moduli of polybutylene succinate/carbon nanotube composites are higher than the neat polybutylene succinate. The processability of polybutylene succinate/carbon nanotubes composites was improved and more pronounced in higher content of carbon nanotubes.